The Implementation of Occupational Health and Safety Using Zerosicks in Indonesia Vocational Education - Ismara, Ketut Ima; Kurniawan, Arie Wibowo; Kasjono, Heru Subaris; Zamtinah, Zamtinah; Mustaqim, Bima; Fathurrahman, Haris Imam Karim; Adnanda, Azka (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
This study aims to determine (1) the implementation of occupational health and safety (OHS) using the Zerosicks method in vocational education and (2) the significant relationship between each aspect of the countenance stake evaluation model. The model consists of 3 stages: input (Antecedent), process (Transaction), and output. Then, the population in this study involved 727 students with a sample size of 258.03, and this research was conducted in April-June 2021 at the Prambanan Muhammadiyah Vocational High School. Furthermore, the data analysis techniques used were quantitative descriptive and SEM (Structural Equation Modeling). The study findings reveal that (1) the antecedent stage, encompassing environment, hazard, risk, knowledge, and standardization indicators, is evaluated as excellent by teachers and predominantly good by students. In the Transaction stage, focusing on risk management control, solution, implementation, and culture indicators, teachers rate it as good to perfect, while students generally rate it as very good to good. Moreover, the output stage, comprising control and OHS behavior awareness indicators, is deemed outstanding by both teachers and students. (2) The indicators of the model are valid and achievable following the results of the confirmatory factor analysis, and the structure of the theoretical model fulfils the Goodness of Fit criteria for empirical data because it has six criteria. Furthermore, an antecedent has a significant effect on Transaction and OHS Output, while a Transaction has a significant effect on OHS Output.